Understanding the dimensions of home for people returning home post stroke rehabilitation. (July 2016) - Hodson, Tenelle; Aplin, Tammy; Gustafsson, Louise
Introduction: Home is a meaningful and important place and the transition to home from hospital is considered a significant point in recovery for people after stroke. Six dimensions of the home environment have previously been described as important for well-being and contributing to one's experience of home: the physical, social, personal, temporal, occupational and societal dimensions. The aim of this study was to understand the experience of home for people with stroke after discharge to home from hospital rehabilitation. Method: A secondary template analysis applied the dimensions of home to semi-structured interviews that explored the transition to home experience for seven participants with stroke at 4–6 weeks post discharge. Results: All six dimensions were present in the descriptions of returning to home from stroke rehabilitation. The social, personal and occupational dimensions appeared to be the most prominent and often centred on loss or change. Conclusion: People returning home after a stroke enter a different home environment than the one they experienced prior to stroke, with changes experienced in all dimensions of home. Closer attention to the dimensions during discharge preparation may enhance the transition experience.